A Matrix Usage for Load Balancing in Shortest Path Routing - Mustafa, Nor Musliza (2009)
The Open Shortest Path First (OSPF) protocol is a hierarchical interior gateway protocol (IGP) for routing in Internet Protocol. Traffic flows routed along shortest path and splits the load equally at nodes where a number of outgoing links on the shortest paths to the same destination IP address. Network operator defines shortest paths based on a link weights value assigned to each link in the network. The OSPF link weight-setting problem seeks a set of link weights to optimize a cost function and network performance, typically associated with a network congestion measure. This research highlight the importance of managing network resource and avoiding congested point in the current widely deployed shortest path routing. The previous Evenly Balancing Method (EBM) and Re-Improved Balancing Method (R-IBM) used demand matrix, which requires constant monitoring of routers with high time executions in the optimization process. The problems are to find another matrix that can replace or minimize the usage of demand matrix with low time executions process. A new proposed Matrix Usage Method (MUM) is developed. MUM selects the shortest path routing in order to provide a balancing load and optimized the usage of link in the network. The simulation results show that the routing performance of the new proposed method MUM is better than the routing performance of the previous Evenly Balancing Methods (EBM) and Re-Improved Balancing Method (R-IBM) due to providing counting selection technique in the shortest path routing. MUM times executions are also improved comparing with the previous work.